The Effect of Yoga on the Sleep Quality of Pregnant Women in the Third Trimester at Pmb Siti Julaeha, Pekan Baru City - Purnamasari, Indah; Amelia, Lucky; Issabella, Chentia Miss (Universitas Prima Indonesia, 2025)
The longer the pregnancy progresses, women expecting a child are likely to face problems with sleep. These sleep issues often arise from the physical discomfort caused by the various changes that occur during pregnancy. Insufficient sleep can result in complications related to pregnancy. The purpose of this study is to ascertain how yoga and relaxation techniques might enhance the quality of sleep for pregnant women in their third trimester at PMB Siti Julaeha Pekanbaru City. This kind of study employs a two-group pretest-posttest quasi-experimental research design. Purposive sampling was utilized to choose 27 intervention groups and 27 control groups from a population of 56 respondents. A PSQI (Pittsburgh Sleep Quality Index) sleep quality measuring questionnaire sheet was employed as the research tool in this study. The analysis from the paired T-test revealed a marked contrast in the sleep quality of participants prior to and following their yoga practice, indicating a significance level of 0.000, which is below the 0.05 threshold. Therefore, it can be concluded that engaging in yoga influences the participants' sleep quality. It is anticipated that pregnant women in their third trimester who practice yoga will have better sleep quality because yoga is an excellent way to improve sleep quality.